Who is in the centre?: Interaction patterns in traditional informal learning events in Kampung Pueh - Burkhardt, Jey Lingam * (Dayak Bidayuh National Association, 2017)
Since the emergence of learner-centred teaching, instructors are required to create learning environments that motivate students to accept responsibility for learning where learners actively participate in their learning process. It is assumed that the practice of peer correction and teamwork, where learners engage with each other in their learning process, are effective techniques. This paper describes interaction patterns among a group of preliterate women in a traditional learning environment. These patterns were observed on two selected spontaneous and uninitiated learning events, nyusup atap ‘making thatched roofs’ and nganyam katupat ‘weaving rice cake casings’, in which proficient/skilled women taught other women their skills. The grounded theory approach (Glaser and Strauss, 1967) was used to generate a “thick” description with keywords in order to provide an inductive method of discovering patterns. A few interesting learning interaction formations emerged, which elucidate the Salako women’s preference to learn from a proficient “teacher” rather than from peers. Some plausible interpretations for this observation are suggested. Finally, this paper concludes with implications for adult educators who employ the learner-centred approach in their classrooms.